HUBUNGAN ANTARA 5 ASPEK QUALITY OF WORK LIFE DENGAN KINERJA DOKTER Survei Pada Dokter RSUD Kota Pinang Tahun 2021 - Sonia, Inka; Handini, Myrnawati Crie; Brahmana, Netti Etalia; Ketaren, S. Otniel; Sitorus, Mido Ester J. (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
The purpose of this study was to determine the significant relationship between the five aspects of QWL with the performance of doctors at the Regional Public Hospital Pinang City in providing health services. This research is a quantitative research which uses a correlational method with a survey approach. This study did not use sample, because from the calculation of the Minimum Sample Size with the Slovin formula, it turned out that the sample size that must be taken also amounted to 39, the same as the total population, namely all doctors at Regional Public Hospital Pinang City at the time this research was conducted. The instrument for the doctor’s performance variable based on ACGME and the QWL variable based on the 2006 Cascio theory which had been tested for reliability and validity not at the research location. Data analysis was carried out by using univariate analysis test, bivariate test with chi-square statistical test, and multivariate test with Anova analysis. The QWL component that has a very significant effect is the available facilities, because the availability of facilities can provide welfare and satisfiy the needs of doctors at work. The least significant component of QWL is career development, because the doctor’s status is a civil servant and the promotion goes according to central regulation not from the hospital management.